(3GdfaGFS GdacQjIs - (3eMeO Hf GdeaVd Hf CMeO GdbdhSjs; (3GHf MLQ GdgjJej , TgGH GdOjf CHhGdYHGS TjN GdGSdGe CMeO Hf eMeO Hf Ydj Hf MLQ GdgjKej GdSYOj GdCfUGQj,J (B974 (3g` s
(3ChdgG (B:s
(3hHYO, aGdeJMJe Ydi cd Pj dH Sdje hUa QShdg GdcQje aj bUjOJg GdoHQOI hGdgeRjI GdYOjeJj GdfXjQ s
(3BNQgG (B:s
(3Gddge Ud hSde Ydi SjOfG hfHjfG hehdGfG eMeO YOO eG PcQc hPcQg GdPGcQhf, hYOI eG Zad Yf PcQc hPcQg GdZGadhf s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B234 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B152s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B159 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1349s
Keywords: (3GdCOHs